Pemanfaatan Fly Ash Sawit Sebagai Katalis Asam Dalam Proses Esterifikasi Gliserol Sebagai Produk Samping Biodiesel Menjadi Triacetin - Triyana Defi; Zuchra Helwani; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Glycerol is a by-product of biodiesel that produced about 10% of the amount of biodiesel. Glycerol can be processed into economic products such as triacetin. Triacetin is a triesther of glycerol and acetic acid that can be applied as additive in the field of food or non food. Triacetin can be produced through estherification of glycerol and acetic acid by using palm fly ash as the solid acid catalyst. The aim of this research was to determined the characteristic of the palm fly ash as solid acid catalyst and determined the influence of the catalyst concentration, mol ratio of reactan and time of estherification toward the conversion of glycerol. Variation that used were concentration of catalyst 1, 2, 3% of acetic acid mass, mol ratio of reactan 1:5, 1:7, 1:9, and time of estherification 1, 2, and 3 hours. The estherification temperature was 100oC. The characteristic of palm fly ash catalyst of acidity, crystallinity, and surface area increasing after activation process. The conversion of glycerol increased by the increasing of catalyst concentration, mol ratio of reactan and time of estherification. The highest conversion gain at concentration of catalyst 1%, mol ratio of reactan 1:9, and time of estherification 3 hours is 47.41%.Keywords: biodiesel, estherification, fly ash, glycerol, triacetin.